1)12x²+3x=0 x(12x+3)=0 12х+3=0 или х=0 х=-4 2)x²-10x=0 х(х-10)=0 х-10=0 или х=0 х=10 3)3x²-6=0 3x²=6 x²=2 x²= корень из 2 или (-) корень из 2 4)4x²+20x=0 4х(х+5)=0 4х=0 или х+5=0 х=0 или х=-5 5)4-36x²=0 36x²=4 x²=1/9 х=1/3 или х=-1/3
1) Вспоминаем и (или) выводим формулы sin (pi + 2a) = -sin 2a sin 3a = sin(2a + a) = sin 2a*cos a + cos 2a*sin a = = 2sin a*cos a*cos a + (1 - 2sin^2 a)*sin a = = sin a*(2cos^2 a - 2sin^2 a + 1) = sin a*(2 - 2sin^2 a - 2sin^2 a + 1) Получаем sin 3a = sin a*(3 - 4sin^2 a) Аналогично cos 3a = cos a*(4cos^2 a - 3) Подставляем (sin a*(1 - 3 + 4sin^2 a)) / (cos a*(1 - 4cos^2 a + 3)) + cos 2a / sin 2a = = tg a*(4sin^2 a - 2) / (4 - 4cos^2 a) + ctg 2a = -2tg a/(4sin^2 a)*cos 2a + ctg 2a = = ctg 2a - sin a/cos a*cos 2a/(2sin^2 a) = ctg 2a - cos 2a/(cos a*2sin a) = = ctg 2a - cos 2a/sin 2a = ctg 2a - ctg 2a = 0
2) У вас опечатка. Вместо = cos(3pi + 2a) должно быть + cos(3pi + 2a) Числитель sin^4 a + 2sin a*cos a - cos^4 a = sin^4 a - cos^4 a + sin 2a = = (sin^2 a + cos^2 a)(sin^2 a - cos^2 a) + sin 2a = 1*(-cos 2a) + sin 2a = = sin 2a - cos 2a = cos 2a*(sin 2a/cos 2a - 1) = cos 2a*(tg 2a - 1) Поэтому дробь равна cos 2a Получаем cos 2a + cos(3pi + 2a) = cos 2a - cos 2a = 0
x(12x+3)=0
12х+3=0 или х=0
х=-4
2)x²-10x=0
х(х-10)=0
х-10=0 или х=0
х=10
3)3x²-6=0
3x²=6
x²=2
x²= корень из 2 или (-) корень из 2
4)4x²+20x=0
4х(х+5)=0
4х=0 или х+5=0
х=0 или х=-5
5)4-36x²=0
36x²=4
x²=1/9
х=1/3 или х=-1/3